Sources and interpretation in ancient Judaism: studies for Tal Ilan at sixty - Pioṭrḳovsḳi, Meron M.; Dönitz, Saskia; Herman, Geoffrey; Ilan, Ṭal (Ancient Judaism and early Christianity, 2018)
Intro -- ‎Contents -- ‎Preface and Acknowledgements -- ‎Abbreviations -- ‎Notes on Contributors -- ‎Tabula Gratulatoria -- ‎Introduction -- ‎I. -- ‎II. -- ‎III. -- ‎Part 1. Second Temple Literature and History -- ‎Chapter 1. Chasing Away Lions and Weaving: The longue durée of Talmudic Gender Icons (Garfinkel) -- ‎Chapter 2. Malthace, Archelaus, and Herod Antipas: Between Genealogy and Typology (Schwartz) -- ‎Chapter 3. A New Perspective on Two Jewish Queens in the Second Temple Period: Alexandra of Judaea and Helene of Adiabene (Liebowitz) -- ‎Chapter 4. Was Hillel a Pharisee? (Werman) -- ‎Part 2. The Jews and the Papyri -- ‎Chapter 5. Ezechiel 33,21--39,29: Anmerkungen zum Profil der Sinneinheit in der nicht-masoretischen Textfassung (Papyrus 967) und zu Veränderungen durch proto-masoretische Redaktoren (Finsterbusch) -- ‎Chapter 6. The Third Century BCE: New Light on Egyptian Jewish History from the Papyri (Hacham) -- ‎Chapter 7. 'Literary Jews:' The Jewish Community of Oxyrhynchus in Light of Non-documentary Texts on Papyrus (Piotrkowski) -- ‎Chapter 8. Shabtai in Egypt: Cultural Interaction between Jews and Egyptians under the Ptolemies (Szántó) -- ‎Part 3. Rabbinic Literature -- ‎Chapter 9. Babylonia of Pure Lineage: Notes on Babylonian Jewish Toponymy (Herman) -- ‎Chapter 10. A Spindle for Caesar's Daughter (Kiperwasser) -- ‎Chapter 11. Rabbinic Forensics: Distinguishing Egg White from Semen in b. Giṭṭin 57a (Baskin) -- ‎Chapter 12. Rabbinic Images of Second Temple Diasporas and Their Links with Judaea: History or Fantasy? (Gafni) -- ‎Chapter 13. Are Parables an Interpretation? (Nikolsky) -- ‎Chapter 14. When a Man Sells His Daughter as an ‮אמה‬‎: The ‮אמה העבריה‬‎ as m. Qiddushin's Role Model for Becoming a Wife (von Bresinsky) -- ‎Chapter 15. Classroom Encounters--An Appreciation (Tzuberi) -- ‎List of Publications of Prof. Tal Ilan.